Development and Validation of a Farmer’s Focused Digital Literacy Scale - Chandra, Saurabh; Ghadei, Kalyan; Chennamadhava, M; Ali, Waris (Indian Journal of Extension Education, 2024)
The research aimed to develop a tool for assessing the digital literacy of farmers towards ICT-led agriculture in India. The study identified three dimensions namely digital knowledge, attitude, and digital competency, for a farmer-focused digital literacy scale. Digital competency consisted of seven sub-dimensions viz device setup, digital communication and collaboration, digital content creation and sharing, digital safety, problem-solving, digital marketing, and digital payment. The digital literacy scale was developed with Likert scale construction methodology. An overall mean relevancy score of 5.693 was obtained. A pilot study was conducted with 60 farmers in a non-sampled area. The t value was calculated, and the cutoff value for item selection was set at > 1.75. For assessing internal consistency reliability using the Spearman-Brown formula, a reliability coefficient of 0.850 was found. The calculation of Cronbach’s alpha gave a value of 0.743, indicating that the scale shows a high level of consistency in its measurement. The standard farmers-focused digital literacy scale comprised of 30 items, and its content validity was determined with expert opinions.
Keywords: Digital literacy; Digital competency; Scale development; Reliability; Validity